Beta-glucan quantification by fluorescence analysis using photonic crystals. Issue 38 (31st March 2016) - Ren, Jiaoyu; Xuan, Hongyun; Zhu, Yanxi; Liu, Xuefan; Ge, Liqin
Abstract : In this study, 1DPhCs were utilized as a Bragg reflection mirror. Gold was deposited on 1DPhC films. 1DPhCs with Au were used for quantitative determination of beta-glucan. Abstract : One-dimensional photonic crystal (1DPhC) was fabricated using a spin-coating method to be utilized as a Bragg reflection mirror. Gold was deposited on 1DPhC films by thermal evaporation under a vacuum. The beta-glucan–fluorochrome complex, whose emission wavelength was largely consistent with the photonic stopband of the 1DPhC, spin coated on the surface of 1DPhC with Au. The fluorescence of beta-glucan–fluorochrome complex deposited on 1DPhCs with Au was obviously enhanced in comparison with that on glass. There was 10-fold fluorescence enhancement. In this study, 1DPhCs with Au were used for the quantitative determination of beta-glucan. Fluorescence spectra demonstrated that a linear relationship existed between the fluorescence intensity and the beta-glucan concentration within 1–6 μg mL −1 . The detection limit for beta-glucan is 0.083 μg mL −1 with a sensitivity of 19.53 mL μg −1 .